Improving the Performance of Credit Agency Employees People Kedonganan Village Through Employee Engagement and Organizational Citizenship Behavior - Ningrum, Safitri; Ardani, Wayan; Widani, Ni Made (Transforma Jurnal Manajemen, 2024)
This study aims to determineThe influence of employee performance at people's credit institutions (LPD) partially and simultaneously on employee engagement and organizational citizenship behavior. Collection is carried out using questionnaires/questionnaires. The sample in this research was 42 employees of the Kedonganan Traditional Village LPD using a saturated sample collection method where all employees were used as the population. The collected questionnaire data was then analyzed using multiple linear regression analysis using quantitative research. Hypothesis testing used the t test and F test. The results of the study showed thatemployee engagementhas a positive and significant effect on the performance of employees of the Kedoganan Traditional Village People's Credit Institution (LPD) (H1 is accepted). Organizational Citizenship Behaviorhas a positive and significant effect on the performance of employees of the Kedoganan Traditional Village People's Credit Institution (LPD) (H2 is accepted). Employee engagement and Organizational Citizenship Behavior simultaneously have a positive and significant effect on the performance of employees of the Kedoganan Traditional Village People's Credit Institution (LPD) (H3 is accepted).It is hoped that the results of this research will enable LPD employees to realize the vision and mission of the institutionnot only carrying out the role as stated in the job description and organizational structure, but also being able to carry out the role beyond the standards stated in the institution.